Out‐of‐Equilibrium (Supra)molecular Systems and Materials 2021
DOI: 10.1002/9783527821990.ch2
|View full text |Cite
|
Sign up to set email alerts
|

Learning from Embryo Development to Engineer Self‐organizing Materials

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 165 publications
(197 reference statements)
0
4
0
Order By: Relevance
“…The timing of internalization can be set either externally by adding a reagent or internally by tuning the initial composition of the medium and taking advantage of a clock reaction. In addition, we have demonstrated that reactive extracellular media may create concentration patterns that spatially control the internalization of DNA by cells, mimicking the transfer of positional information at play during early embryo development. ,, Importantly, these patterns were generated autonomously by nonequilibrium chemical reactions without hydrodynamic flow, in contrast with standard methods relying on microfluidics, where flow introduces shear stress and washes out nutrients and signaling molecules.…”
Section: Discussionmentioning
confidence: 99%
“…The timing of internalization can be set either externally by adding a reagent or internally by tuning the initial composition of the medium and taking advantage of a clock reaction. In addition, we have demonstrated that reactive extracellular media may create concentration patterns that spatially control the internalization of DNA by cells, mimicking the transfer of positional information at play during early embryo development. ,, Importantly, these patterns were generated autonomously by nonequilibrium chemical reactions without hydrodynamic flow, in contrast with standard methods relying on microfluidics, where flow introduces shear stress and washes out nutrients and signaling molecules.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, couplings between RD and AM have not yet been engineered in vitro. However, recent experimental developments suggest that mechano-chemical self-organization could be investigated in well-controlled in vitro experiments in the near future [27]. Such in vitro systems, which we will call reactiondiffusion active matter (RDAM) systems, would be particularly interesting for quantitatively testing theoretical predictions concerning the propagation of a reacting and diffusing activity regulator -a situation that is likely to be ubiquitous in in vivo settings.…”
Section: Introductionmentioning
confidence: 99%
“…Although a wide array of AM experimental systems exist, we will restrain ourselves to molecular active matter because we believe that it has the highest chance to be combined with molecular RD systems. In this category, extracts of cytoskeletal filaments and motors, either actomyosin or kinesin/microtubule gels [27,28], are particularly suitable. Depending on the situation, these gels are locally contractile or extensile and are composed of polar, nematic or isotropic particles [29].…”
Section: Introductionmentioning
confidence: 99%
“…This is performed by chemical reactions that link the concentration of a trigger to the force exerted by the active gel . Despite its importance in the development of life-like synthetic materials, , engineering such a chemomechanical trigger remains challenging. An important body of work has developed methods to chemically actuate hydrogels; , however, the current approaches either pattern passive hydrogels or trigger deformations in active gels with chemical reactions that are difficult to design. , …”
mentioning
confidence: 99%